Clustering Preserving Projections for High-Dimensional Data. (December 2020) - Cai, Weiling; Zhou, Honghan; Xu, Le
Abstract: In this paper, a novel clustering preserving projection method is presented to retain the cluster (or group) structures hidden in the original data. This method involves two steps: (1) the famous clustering method Fuzzy c-means is utilized to discover the cluster distribution in data; (2) such distribution is preserved by finding a linear embedding that minimizes the intra-cluster compactness in low-dimensional space. The feasibility and effectiveness of the proposed method are demonstrated on UCI dataset and USPS digital handwritten dataset.